Artificial Intelligence for marketing communication: moral dilemma, ethics, and customer satisfaction - Y. Wahyu Agung Prasetyo; Luis T. Santos; Hayari; Kurniati Abidin; Dhety Chusumastuti (Jurnal Studi Komunikasi, 2023)
Artificial Intelligence (AI) represents a remarkable technological innovation that has been developed by human beings in the wake of the global COVID-19 pandemic, which has had devastating consequences. In order to ensure their survival in the future, humans are reliant upon the development and utilisation of tools. However, the acceptance of artificial intelligence (AI) within the human population has its own set of challenges and concerns. There exists a divergence of opinions on the validity of artificial intelligence (AI) and some individuals even perceive the notion of AI as irrational. Nevertheless, it is important to acknowledge that AI serves a significant purpose beyond its capacity to exhibit remarkable capabilities. The remarkable abilities possessed by AI instil apprehension in humans, as there is a concern that they may eventually be superseded by AI to the point where humans are left with no role or purpose. The emergence of AI also exemplifies the challenges that accompany technological progress.